2019
DOI: 10.1088/1757-899x/543/1/012075
|View full text |Cite
|
Sign up to set email alerts
|

Production of Liquid Smoke From the Process of Carbonization of Durian Skin Biomass, Coconut Shell and Palm Shell for Preservation of Tilapia Fish

Abstract: The Liquid smoke can be use for food preservation, be obtained from pyrolysis of materials containing cellulose, hemicellulose, and lignin. The form of liquid smoke that has the ability to preserve,for their phenolic compounds,acids and carbonyl. The purpose of this research is to know the quality of liquid smoke from process of charcoal the biomass obtained from rotary pyrolysis carbonisator as fish preservative, the effect of liquid smoke on the chemical and organoleptic properties of fish, and the resilienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 2 publications
0
4
0
2
Order By: Relevance
“…The pH value represents a crucial parameter used to gauge the quality of the distillation product, offering valuable insights into the chemical decomposition processes within coconut shells that yield organic acids present in liquid smoke [21]. Previous research endeavours have shed light on this aspect; Anggraini and Yuniningsih [22] reported a pH value of 1.41 for liquid smoke derived from coconut shells, while Sari et al, [15] observed a pH value of 2.4 for coconut shell liquid smoke subjected to redistillation using the vacuum method at 81°C. Further research by Saloko et al, [23] yielded a pH value of 2.54 for the redistillation of coconut shell liquid smoke at 98±2°C.…”
Section: Ph Value Of Coconut Shell Liquid Smoke Distillation Productmentioning
confidence: 99%
See 1 more Smart Citation
“…The pH value represents a crucial parameter used to gauge the quality of the distillation product, offering valuable insights into the chemical decomposition processes within coconut shells that yield organic acids present in liquid smoke [21]. Previous research endeavours have shed light on this aspect; Anggraini and Yuniningsih [22] reported a pH value of 1.41 for liquid smoke derived from coconut shells, while Sari et al, [15] observed a pH value of 2.4 for coconut shell liquid smoke subjected to redistillation using the vacuum method at 81°C. Further research by Saloko et al, [23] yielded a pH value of 2.54 for the redistillation of coconut shell liquid smoke at 98±2°C.…”
Section: Ph Value Of Coconut Shell Liquid Smoke Distillation Productmentioning
confidence: 99%
“…The initial phase targets the removal of harmful compounds, while a subsequent redistillation stage seeks to isolate pure phenol compounds. Phenol's diverse attributes, encompassing antioxidative, antibacterial, and antifungal properties, extend its potential utility to food preservation [9,[12][13][14][15][16]. Thus, the study's primary objective is to establish optimal conditions that yield enhanced quantities of coconut shell liquid smoke, simultaneously maximizing phenol content.…”
Section: Introductionmentioning
confidence: 99%
“…Proses pengolahan ikan asap secara tradisional masih menggunakan sistem terbuka. Kekurangan pengasapan ini antara lain penampakan ikan kurang menarik, kesulitan dalam mengontrol suhu, dan menimbulkan polusi udara (Sari et al, 2019). Proses pengasapan terbuka juga beresiko terkontaminasi oleh debu kotoran atau mikroorganisme yang dapat menghasilkan produk yang kurang higienis sehingga tidak aman dikonsumsi (Ibanga et al, 2019).…”
Section: Daftar Rujukanunclassified
“…The liquid smoke resulting from pyrolysis is then purified by the distillation method. 500 mL of liquid smoke, then boiled to a temperature of 100˚C [20]. From the process of making liquid smoke, there are three types of liquid smoke solutions with different boiling points, namely liquid smoke without distillation (A) at 0˚C -400˚C, liquid smoke residue (B) at 100 0 C -400˚C and liquid smoke distillate (C) 0˚C -100˚C.…”
Section: ) the Procedures Of Making Liquid Smokementioning
confidence: 99%